UJI DAYA HAMBAT EKSTRAK SEREH WANGI (Cymbopogon nardus L.) UNTUK MENEKAN PATOGEN CENDAWAN Colletotrichum capsici PENYEBAB PENYAKIT ANTRAKNOSA PADA CABAI (Capsicum annum) SECARA IN VITRO - B, Fatmia; Lakani, Irwan; Edy, Nur (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The objective of this research was to find the suitable concentration of citronella extract that can effectively hinder the growth of C. capisici colonies responsible for chili pod rot in a controlled environment (in vitro). The study was conducted at the Laboratory of Plant Diseases, Faculty of Agriculture, Tadulako University, in July 2018. The research employed a completely randomized design (CRD) with four treatments and a control group, named ES0 (0% concentration, control), ES1 (0.3% concentration), ES2 (0.6% concentration), and ES3 (0.9% concentration), and ES4 (1.2% concentration). The experiment was repeated three times. The study demonstrated that as the concentration of citronella extract increased, the inhibition of fungal colony growth also increased. The most effective inhibition was observed with a 1.2% concentration of citronella extract, which was significantly different from the other treatments.